The Influence of Metacognitive Strategies and Critical Thinking Skills on the Reading Comprehension of Eighth-Grade Students - Yarniati, Miftahu Rizqoh; Zulhidah; Ansyari, Muhammad Fauzan (IJLHE: International Journal of Language, Humanities, and Education, 2025)
This study investigates the influence of metacognitive strategies and critical thinking skills on reading comprehension among eighth-grade students at MTsN 6 Kampar. The research addresses students’ difficulties in identifying main ideas, making inferences, and applying reading strategies, which contribute to low comprehension levels. A quantitative approach with multiple regression analysis was employed, involving 60 students selected through random sampling. Data were collected using reading comprehension tests, a metacognitive strategies questionnaire, and a critical thinking skills test. The results revealed that both metacognitive strategies and critical thinking skills significantly influenced reading comprehension individually and simultaneously. Students who effectively applied metacognitive strategies and demonstrated higher critical thinking skills achieved better reading comprehension scores. The findings underscore the importance of integrating these skills into instructional practices to foster independent, reflective, and strategic readers. Future research is recommended to explore similar approaches in different educational contexts and with larger samples to validate the findings.